Analisis Kemampuan Literasi Bahasa dalam Konteks Pembelajaran Biologi - Jihan Azhaar Ramadhanty; Vita Meylani; Edi Hernawan (BIOEDUSCIENCE, 2020)
Background: The results of PISA showed that Indonesian students' literacy skills in the field of science are still low. Until now, the cause of the problem is still little information reported. This study was conducted to analyze the language literacy skills of students in biological learning contexts. Methods: the methods used in the research is mixed methods research. This research involved 72 science program students who were selected by purposive sampling. The data were gained by observations, interviews and giving the posttest consisting of 17 questions of multiple-choice based on the Programme for International Student Assessment (PISA) indicator for language literacy in biological learning. Results: That the analysis of language literacy in the context of Biological learning has an excellent literacy with a high category. The research showed that the highest average grade of language literacy was in the integrate and interpret aspects of 75,00. Meanwhile, the lowest average grade in the reflect and evaluate aspects was 57,00. The average overall grade in the language literacy on Biological learning was 70,22. Conclusion: Sustainable literacy activities stimulate higher-order thinking skills, especially in the field of science, because language literacy skills can indirectly affect students' outcomes on scientific skills.